2017
DOI: 10.1186/s12998-017-0139-x
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar lordosis in prone position and prone hip extension test: comparison between subjects with and without low back pain

Abstract: BackgroundProne hip extension (PHE) is a common and widely accepted test used for assessment of the lumbo-pelvic movement pattern. Considerable increased in lumbar lordosis during this test has been considered as impairment of movement patterns in lumbo-pelvic region. The purpose of this study was to investigate the change of lumbar lordosis in PHE test in subjects with and without low back pain (LBP).MethodA two-way mixed design with repeated measurements was used to investigate the lumbar lordosis changes du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…One possible explanation is that patients use an altered trunk muscle activation strategy to stiffen their lumbopelvic region to minimize shear forces or pain. This explanation was supported by several studies in which they found less lumbopelvic motion during functional tasks . Because conflicting evidence still exists, investigation of lumbopelvic movement and trunk muscle activation strategy is needed to clarify this issue.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…One possible explanation is that patients use an altered trunk muscle activation strategy to stiffen their lumbopelvic region to minimize shear forces or pain. This explanation was supported by several studies in which they found less lumbopelvic motion during functional tasks . Because conflicting evidence still exists, investigation of lumbopelvic movement and trunk muscle activation strategy is needed to clarify this issue.…”
Section: Introductionmentioning
confidence: 88%
“…The main objective of this study was to determine the differences in lumbopelvic motion and muscle activation pattern between patients with nonspecific LBP and healthy individuals during PHE. Based on current evidence, we expected that patients with nonspecific LBP would demonstrate a difference in the amount of lumbopelvic motion. In addition, we further hypothesized that patients would demonstrate altered trunk muscle activation patterns.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lifetime prevalence of LBP is reported to be as high as 84% 3 . Radiculopathy is a common cause of low back and leg pain 4 .…”
Section: Introductionmentioning
confidence: 99%